Compartmental modulation of abdominal Hox expression by engrailed and sloppy-paired patterns the fly ectoderm - Gebelein, Brian (2007)
In Drosophila, segmentation genes partition the early embryo into reiterative segments along the anterior-posterior axis, while Hox genes assign segments their identities. Each segment is also subdivided into distinct anterior (A) and posterior (P) compartments based on the expression of the engrailed (en) segmentation gene. Differences in Hox expression often correlate with compartmental boundaries, but the genetic basis for these differences is not well understood. In this study, we extend previous results to describe a genetic circuit that controls the differential expression of two Hox genes, Ultrabithorax (Ubx) and abdominal-A (abd-A), within the A and P compartments of the abdominal ectoderm. Consistent with earlier findings, we show that en is essential for high Abd-A levels and low Ubx levels in the P compartment, whereas sloppy-paired (slp) is required for high Ubx levels in the A compartment. Overall, these results demonstrate that the compartmental expression of Ubx and abd-A is established through a repressive regulatory network between en, slp, Ubx and abd-A. We also show that abd-A expression in the P compartment is important for the formation of abdominal-specific cell types, suggesting that en and slp modulation of Hox expression within the A and P compartments is essential for embryonic patterning.